Decarbonization Investment Strategies in an Uncertain Climate - Adam Michael Bauer; Florent McIsaac; Stéphane Hallegatte (Earth's Future)
Abstract The Paris Agreement established that global warming should be limited to “well below” 2 °C and encouraged efforts to limit warming to 1.5 °C. Achieving this goal presents a challenge, especially given (a) adjustment costs, which penalize a swift transition away from fossil fuels owing to, for example, skilled labor scarcity, and (b) climate uncertainty that complicates the link between emissions reductions and global warming. This paper presents a modeling framework that explores optimal decarbonization investment strategies with adjustment costs and climate uncertainty. The findings show that climate uncertainty impacts investment in three ways: (a) the cost of policy increases, especially when adjustment costs are present; (b) abatement investment is front‐loaded relative to a scenario without uncertainty; and (c) the sectors with the largest changes in investment are those that are “hard‐to‐abate”, such as heavy industry and agriculture, each of which have high investment costs and annual emission rates. The longer learning about climate uncertainty is delayed, the more these impacts are amplified. Each of these effects can be traced back to the carbon price distribution inheriting a “heavy tail” when climate uncertainty is present. The paper highlights how climate uncertainty and adjustment costs combined lead to heightened urgency for near‐term investments in decarbonization.